Size does matter: can we reduce the radiotherapy field size for selected cases of anal canal cancer undergoing chemoradiation? - Crowley, C; Winship, A; Hawkins, M; Morris, S; Leslie, MD (2009)
AIMS: Chemoradiation is the standard of care for the treatment of anal canal cancer, with surgery reserved for salvage. For tumours with uninvolved inguinal nodes, it is standard to irradiate the inguinal nodes prophylactically, resulting in large field sizes, which contribute to acute and late toxicity. The aim of this single-centre retrospective study was to determine if, in selected cases, prophylactic inguinal nodal irradiation could be avoided. MATERIALS AND METHODS: Between August 1998 and August 2004, 30 patients with biopsy-proven squamous cell anal canal cancer were treated with chemoradiation using one phase of treatment throughout. A three-field beam arrangement was used without attempting to treat the draining inguinal lymph nodes prophylactically. The radiotherapy dose prescribed was 50Gy in 25 daily fractions over 5 weeks. Concomitant chemotherapy was delivered with the radiation using mitomycin-C 7-12mg/m(2) on day 1 and protracted venous infusional 5-fluorouracil 200mg/m(2)/day throughout radiotherapy. RESULTS: All patients had clinically and radiologically uninvolved inguinal and pelvic nodes and all had primary lesions that were T3 or less. The median age at diagnosis was 65 years (range 41-84). The median follow-up was 41 months (range 24-113). The mean posterior field size was 14x15cm and the mean lateral field size was 12x15cm. All patients achieved a complete response. Ninety-four per cent of patients (28/30) were alive and disease free. The two patients who died did so of unrelated causes and were disease free at death. Four patients relapsed and all were salvaged with surgery; two for local disease requiring abdominoperineal resection, one with an inguinal nodal relapse requiring inguinofemoral block dissection and one for metastatic disease to the liver who underwent liver resection. CONCLUSIONS: This single-centre retrospective study supports the treatment for selected cases of anal canal cancer with smaller than standard radiation fields, avoiding prophylactic inguinal nodal irradiation. Hopefully this will translate into reduced acute and late toxicity. In future studies we would suggest that consideration is given as to whether omission of prophylactic inguinal nodal irradiation for early stage tumours should be explored.